Epithelial-mesenchymal transition and inflammation at the site of the primary tumor - Dominguez, Charli (Semin Cancer Biol, 2017)
Tumor growth and progression are the products of complex signaling networks between different cell types within the tumor and its surrounding stroma. In particular, established tumors are known to stimulate an inflammatory reaction via the secretion of cytokines, chemokines, and growth factors that favor the recruitment of a range of infiltrating immune cell populations into the tumor microenvironment. While potentially able to exert tumor control, this inflammatory reaction is typically seized upon by the tumor to promote its own growth and progression towards metastasis. This review focuses on recent advances in understanding how an established tumor can initiate an inflammatory response via the release of pro-inflammatory mediators, such as IL-6 and IL-8, and their roles in cancer metastasis. In particular, the role of the epithelial-mesenchymal transition (EMT), a phenotypic switch observed in carcinomas that promotes progression towards metastasis, is discussed here in relation to cancer inflammation.